Ocular Manifestations of Chikungunya Infection: A Systematic Review - Liziane Cristine Malaquias da Silva; Fernanda da Silva Platner; Lauany da Silva Fonseca; Virgílio Frota Rossato; Dian Carlos Pereira de Andrade; João de Sousa Valente; Susan Diana Brain; Elizabeth Soares Fernandes (Pathogens, 2022)
The Chikungunya virus (CHIKV) can cause long lasting symptoms and manifestations. However, there is little information on which ocular ones are most frequent following infection. We performed a systematic review (registered in the International Prospective Register of Systematic Reviews; no CRD42020171928) to establish the most frequent ocular manifestations of CHIKV infection and their associations with gender and age. Articles published until September 2020 were selected from PubMed, Scielo, Cochrane and Scopus databases. Only studies with CHIKV-infected patients and eye alterations were included. Reviews, descriptive studies, or those not investigating the human ocular manifestations of CHIKV, those with patients with other diseases and infections, abstracts and studies without relevant data were excluded. Twenty-five studies were selected for inclusion. Their risk of bias was evaluated by a modified Newcastle-Ottawa scale. The most frequent ocular symptoms of CHIKV infection included ocular pain, inflammation and reduced visual acuity, whilst conjunctivitis and optic neuritis were the most common manifestations of the disease. These occurred mostly in individuals of 42 ± 9.5 years of age and woman. The few available reports on CHIKV-induced eye manifestations highlight the need for further research in the field to gather more substantial evidence linking CHIKV infection, the eye and age/gender. Nonetheless, the data emphasizes that ocular alterations are meaningful occurrences of CHIKV infection which can substantially affect quality of life.